Sunday

April 20, 2014

April 20, 2014

Posted by **Peter** on Sunday, February 19, 2012 at 10:36pm.

10^(2x^(2)-5x+11) = 10000

9^(2(x-1)) = √(27)

- Algebra 2 -
**Steve**, Monday, February 20, 2012 at 11:19amjust undo the operations, one by one:

10^(2x^(2)-5x+11) = 10000

take log base 10

2x^(2)-5x+11 = log10000 = 4

2x^2 - 5x + 7 = 0

(2x-7)(x+1) = 0

. . .

9^(2(x-1)) = √(27) = 3^(3/2) = 9^(3/4)

take log base 9

2(x-1) = 3/4

8x-8 = 3

8x = 11

. . .

**Related Questions**

Pre Cal long problem( Can I see the work on this) - A stuffed animal dealer ...

trigonometry - Use logarithms and the law of tangents to solve the triangle ABC...

Math - Solving Logarithms equation - Solve the equation below. Please show all ...

trigonometry - okay so i have this trigonometry problem were i HAVE to use ...

Algebra-please check my answers - Solve the equation by expressing each side as ...

math - Use logarithms to solve expenential equation 5^x=38

kahyla - use the properties of logarithms to write the expression as a sum or ...

trigonometry - Use logarithms and the law of tangents to solve the triangle ABC...

exponential equation-Algebra - Solve the exponential equation. Express the ...

Algebra 2 - How do you solve this exponential equation using logarithms? 2*5^x=...